2005
DOI: 10.1021/bm0504936
|View full text |Cite
|
Sign up to set email alerts
|

From Ultrathin Capsules to Biaqueous Vesicles

Abstract: The layer-by-layer (LbL) adsorption of anionic polyelectrolytes (PE) and tobramycin sulfate (TbS) multilayers on zinc oxide core particles followed by the controlled core-removal process leads to the formation of ultrathin capsules, which gradually convert to biaqueous vesicles and emulsionlike systems depending on the hydrophilicity/hydrophobicity of the PE backbone, PE/TbS ratio, and Zn2+ concentration. The unique characteristics of the PE/TbS multilayer capsules result because of the formation of PE/TbS/H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The vesicle wall thickness is about 23 nm according to the Bragg equation of d = 2π q −1 determined by the small-angle X-ray scattering (SAXS) experiment ( Fig. 2h) 33,34 , which agrees well with the SEM results. The self-assembly of THPG 11 also generated spherical vesicles according to the TEM image ( Supplementary Fig.…”
Section: Preparation and Characterization Of Thpg Polymer Vesiclessupporting
confidence: 82%
See 1 more Smart Citation
“…The vesicle wall thickness is about 23 nm according to the Bragg equation of d = 2π q −1 determined by the small-angle X-ray scattering (SAXS) experiment ( Fig. 2h) 33,34 , which agrees well with the SEM results. The self-assembly of THPG 11 also generated spherical vesicles according to the TEM image ( Supplementary Fig.…”
Section: Preparation and Characterization Of Thpg Polymer Vesiclessupporting
confidence: 82%
“…The photothermal conversion efficiency (η), was calculated using the following Eq. (1) 16,[33][34][35] .…”
Section: Methodsmentioning
confidence: 99%
“…The two complexes phase separate in water as high-density liquid and viscous liquid droplets that converts to a sticky, plastic, and semisolid/solid complex, respectively, on addition of Zn 2+ ions. The two complexes air-dry as a glassy material with different properties described elsewhere . Analogously, variations in the yield of the capsules were obtained after decomposition of [PE/TbS] n @ZnO cores.…”
Section: Resultsmentioning
confidence: 99%
“…19 In the LbL method, oppositely charged polymers are sequentially layered onto the surface of the template. 20 For medical applications, the use of highly charged polymer materials may not be preferred since polyelectrolytes have known biological activities, such as anti-or procoagulation and protein binding. [21][22][23] Polycations often demonstrate the added problem of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been employed to fabricate polymer-based micro- and nanocapsules including self-assembly of amphiphlic block copolymers, layer-by-layer (LbL) coating, and interfacial or surface polymerization. Bates et al have demonstrated the utility of block copolymers self-assembled into “polymersomes”, which may be cross-linked within the hydrophobic region of the shell to improve the physical stability of these capsules. , In comparison to liposomes, polymersomes have demonstrated robust stability, acceptable drug loading, and controlled release. , The processes to fabricate hollow capsules by LbL and polymerization methods typically rely on the deposition of polymer films onto the surface of core templates such as colloidal silica, CaCO 3 , etc., followed by the removal of the templates by appropriate chemical etching . In the LbL method, oppositely charged polymers are sequentially layered onto the surface of the template . For medical applications, the use of highly charged polymer materials may not be preferred since polyelectrolytes have known biological activities, such as anti- or procoagulation and protein binding. Polycations often demonstrate the added problem of toxicity …”
Section: Introductionmentioning
confidence: 99%